(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background and Aim: Denture adhesives were introduced in the field of dentistry with the prime endeavor of providing retention to loose dentures. Currently several brands and forms of denture adhesives are available for denture wearers. However, selection of the perfect adhesive is highly subjective and must be done very carefully. This in vivo study was conducted to assess the retention efficiency of three powdered denture adhesives in maxillary single complete denture of institutionalized patients. Materials and Methods: This study included total 60 patients in which maxillary single complete denture were constructed in last two years. Three commercially available denture adhesives (Fixon, Poligrip, Fittydent ) were studied for their retention performance. All patients were divided into three groups of 20 each with respective adhesives. Group 1 utilized powder Fixon, Group 2 utilized powder Poligrip and Group 3 utilized powder Fittydent for retaining their maxillary complete denture. The measurements were attempted after one month of successful wearing of the denture. Readings were taken separately at 1 hour, 2 hour, 3 hours and 4 hours post wearing by digital force gauge. The metallic hook tip of force gauge was engaged in the labial sulcus for seeing the force. P values less than 0.05 was considered as significant. Statistical Analysis and Results: Total 17 were in the age group of 46-50 years, 28 subjects were of 51-55 years of age, 11 were 56-60 years of age and 4 patients were of age 61-65 years. P value was reported to be significant for first age group (0.02). For Group 1 the statistical mean at 1 hour, 2 hours, 3 hours and 4 hours were 2.43, 2.65, 2.76 and 2.23 respectively. For Group 2 the statistical mean calculated at 1 hour, 2 hours, 3 hours and 4 hours were 1.93, 2.25, 2.02 and 2.12 respectively. For Group 3 the statistical mean at 1 hour, 2 hours, 3 hours and 4 hours were 3.32, 3.02, 2.71 and 2.36 respectively. Comparison among the three study groups using one-way ANOVA revealed highly significant values for level of significance (0.001). Conclusion: Within the limitations of the study, authors concluded that denture adhesive unquestionably increases the retention performance of the maxillary complete denture. In the present study, Fittydent powder showed higher retention when compared to other two tested adhesives. Poligrip powder showed minimum retention among all three adhesives. However, the variation in the acceptance and familiarity of the denture adhesives among population needs to be sought.